Pengaruh Saluran Distribusi, Persepsi Harga dan Ketersediaan Produk terhadap Kepuasan Konsumen Gas Elpiji PT Arie Mulya Barutama Semarang - Aulia Akbar Raynaldo Priyambodo; Ida Martini Alriani (Dharma Ekonomi, 2024)
The purpose of this research is to determine the influence of distribution channels, price perceptions, product availability on consumer satisfaction at PT. Arie Mulya Barutama Semarang. The population of this study was 140 customers. The samples taken using saturated sampling techniques were 140 respondents. This research data analysis tool uses multiple linear regression. The research results show that Distribution Channels have a positive effect on Consumer Satisfaction. This is shown by the calculated t value of 4.758 >1.655, with a sig value. equal to 0.000 < 0.05 (significant). Price Perception has a positive effect on Consumer Satisfaction. This is shown by the calculated t value being greater than the t table, namely 3.312 > 1.655, with a sig value. equal to 0.001<0.05 (significant). Product Availability has a positive effect on Consumer Satisfaction. This is shown by the calculated t value, which is 3.953 > 1.655, with a sig value. equal to 0.000 < 0.05 (significant).